Experimental test of the ecosystem impacts of the keystone predator Triops cancriformis (Branchiopoda: Notostraca) in temporary ponds. (2nd June 2016) - Waterkeyn, Aline; Grillas, Patrick; Brendonck, Luc
Summary: Keystone species can influence an ecosystem through a series of trophic (both direct and indirect) and non‐trophic effects. In temporary ponds, tadpole shrimps were recently identified as keystone predators, but the full extent of their ecosystem impact is still poorly known. Using a large‐scale mesocosm experiment, we quantified the impact of different Triops cancriformis densities on ecosystem properties: water quality (including chlorophyll a as measure for phytoplankton biomass) and the diversity and structure of macrophyte and zooplankton communities. Mesocosms of 400 L (1 m 2 surface) were lined with natural pond sediment of two study ponds differing in their natural Triops densities ( Triops‐ rich and Triops ‐poor pond) and inundated to allow hatching from the egg bank. Afterwards, four Triops density treatments were established in the mesocosms: 0 (control), 5, 25 and 100 Triops per m 2 . After 13 weeks, the two highest Triops densities significantly influenced the ecosystem functioning not only by triggering changes in the diversity and composition of the pond communities but also by affecting water quality through bioturbation. These results confirm that tadpole shrimp can function as ecosystem engineers in temporary ponds and could promote a shift from a clear water to a turbid state through a series of trophic and non‐trophic level effects.